Researchers rush to save oil palm - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Cause for concern in Latin America: Brazilian oil palm plantations of the highly productive African variety of Elaeis guineensis have been decimated by a deeply destructive disease, of which nothing is know for the moment : heart rot (amarelecimento...